PNEUMONITIS HIPERSENSITIF SEBUAH TINJAUAN PUSTAKA - Marwa Zileikhadira Manzalina (Yayasan Pendidikan Medika Indonesia, 2023)
Hypersensitive Pneumonitis (HP) is an inflammatory lung disease caused by type 3 and 4 hypersensitivity reactions to allergens present in the environment and arises after chronic exposure, usually associated with inhaled residential or occupational allergens. The disease is relatively difficult and rare, but can cause significant and irreversible disability. The presence of pulmonary fibrosis on HRCT has important implications for prognosis and management. Patients with HP should be monitored regularly to assess progression. As far as possible, trigger antigens should be avoided. Immunosuppression is commonly used in the treatment of HP but has not been shown to slow the progression of fibrosing disease. Nintedanib, a tyrosine kinase inhibitor, is an approved treatment option for fibrotic HP with a progressive phenotype. Keywords: Hypersensitivity pneumonitis, HRCT, management